Studies on Schistidium (Grimmiaceae, Bryophyta) in Europe, with particular reference to the Alps: I. A description of S. marginale sp. nov. - Blom, Hans H.; Bednarek-Ochyra, Halina; Ochyra, Ryszard (Phytotaxa, 2016)
Schistidium marginale is described as a new species from several European states including Austria, Georgia, Italy, Macedonia, Spain, Switzerland and Turkey. The species is fully illustrated, its affinities are discussed in detail and its current distribution is mapped. The new species is closely related to S. confertum and S. echinatum from which it differs in having a coarser and thicker costa which is 3–4-stratose in mid-leaf and 4-layered at the base; strongly thickened, 2–4-stratose and (1–)2–5-seriate leaf margins; and a thicker and stiffer leaf hair-point. It clearly belongs to Schistidium Bruch & Schimp. sect. Conferta (Vilh.) Ochyra on account of the distinct 3–6(–7)-seriate basal marginal border of quadrate to short-rectangular, often subhyaline cells with distinctly thickened transverse walls.